Jogos Sérios para Auxiliar o Exercício Cognitivo de Idosos Utilizando o Robô Social EVA - Silva, Pedro Lucas Pereira da; Cecim, João Vitor Carvalho; Rocha, Marcelo Marques da; Muchaluat-Saade, Débora C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
Socially Assistive Robots (SARs) are a new class of robots that are designed to engage in social interactions with humans. This paper proposes some Serious Games for the SAR called EVA, detailing how these games can be used in cognitive therapy for older adults. The applications developed for robots not only promote cognitive stimulation and mental health but also aim to improve the overall quality of life of older adults promoting greater independence and reducing feelings of loneliness. This study highlights the potential of SARs in transforming cognitive care and highlights the broader implications for the integration of robotics in older adult care.